Retinal vessel flicker light responsitiviness and its relation to analysis protocols, static and metabolic data in healthy subjects - Artemiev, Dmitri; Todorova, Margarita (Acta ophthalmologica (Oxford, England), 2025)
Aims/Purpose: To assess agreement between different analysis protocols for determination of retinal vessel dilation response to flicker light (FL) and its relation to static‐ and metabolic parameters of retinal vessels in healthy subjects. Methods: 24 right eyes of 24 healthy controls (mean age: 35.87 ±SD 14.20 years), who underwent dynamic‐ and static retinal diameter‐ and oxygen saturation measurements on Retinal Vessel Analyser were included (RVA, Imedos, Jena, Germany). Using repeated video analyses, responses to FL were measured within the superior‐temporal (ST) area. Taking the length and the location into account, the FL data were evaluated in 3 groups: length < 1 optic disc (OD) (group 1); length > 1OD: close to the OD (group 2) and within the VesselMap area (group 3). For comparability, the static‐ (CRA, CRV, AVR) and oxygen saturation parameters (A‐V SO2, V‐SO2, A‐V SO2) were calculated in the ST peripapillary area using the VesselMap tool of RVA and were evaluated in relation to the corresponding dynamic ones (group 3). Results: In all groups, vascular FL response of arteries was less pronounced compared to venules (p = 0.023). Event thought, FL responses (mean ±SD: FL‐A; FL‐V, %) in group 1 to be more pronounced (mean 3.36 ±2.31; 4.42 ±1.69) compared to those in groups 2 (mean: 2.97 ±2.40; 4.08 ±1.55) and 3 (2.84 ±2.29; 4.21± 2.03) they did not reach statistically significant values (p > 0.44). The mean flicker response of venules showed negative correlations to the corresponding static‐ and metabolic parameters: CRV (r = ‐0.489; p = 0.015) and V‐SO2 (r = ‐0.375; p = 0.001). Conclusions: Our study confirms, that flicker light response, even showing slight difference about its length and location, allows agreeable measurements. However, even in healthy subjects, the effect of the static‐ and metabolic retinal vessel measurements on retinal venular flicker response should be taken in consideration.